Study of Quantitative and Qualitative Composition of Low-Molecular Protein-Peptide Compounds of Tenebrio molitor Larvae before and after Cold Acclimation - Tretyak, Diana V.; Gulevsky, Aleksandr K. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):180.